National State Variation of German Phraseology. Antropocentric, Cognitive and Corpus-based Approache - Ostapovych, Oleg (Journal of Vasyl Stefanyk Precarpathian National University, 2015)
The article deals with the elaboration of the modern theoretical concept in study of the variation of German phraseology abroad Germany. It is based on the synthesis of the theory of equal-righted pluricentrism and the hypothesis of double linguistic additivity with the new achievements of the cognitive linguistics. As a result the notions of the «non-predominant national state linguistic variant» different from the regional, normatively non-codified and dialectal variation, cluster variant idiomatic thesaurus, national communicative area in the sphere of phraseology have been introduced. The empirical reality of the categories of «national phraseological system/microsystem», «pluricentric archisystem», «correlation hierarchy», «phraseological world picture», «phraseological concept» have also been falsified